Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1093/carcin/19.5.827
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of small G protein isoprenylation by anticancer monoterpenes in in situ mammary gland epithelial cells

Abstract: Monoterpenes have been shown to both prevent and treat mammary cancer in animal models and are currently in clinical testing in advanced cancer patients. In this study, we investigated a biochemical modulation associated with the antitumor activity of monoterpenes, the inhibition of protein isoprenylation in monoterpene chemoprevention target tissue, i.e. the in situ mammary gland epithelial cells. We first developed a new methodology that for the first time permitted the study of protein isoprenylation and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 41 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Adaramoye et al [24] also showed the antiproliferative effect of X. aethiopica extract on human cervical cancer cells. On the other hand, it was reported that components such as terpinen-4-ol and α-cadinol which are found in all the tested essential oils presented activity against breast, colon, gastric, lung, ovarian and laryngeal cancer cell lines [25]. In addition, β-pinene which is one of the most naturally occurring monoterpene found in the oil of Xylopia species, has shown a significant cytotoxic activity against breast cancer and epidermal skin cancer cell lines [26].…”
Section: Resultsmentioning
confidence: 99%
“…Adaramoye et al [24] also showed the antiproliferative effect of X. aethiopica extract on human cervical cancer cells. On the other hand, it was reported that components such as terpinen-4-ol and α-cadinol which are found in all the tested essential oils presented activity against breast, colon, gastric, lung, ovarian and laryngeal cancer cell lines [25]. In addition, β-pinene which is one of the most naturally occurring monoterpene found in the oil of Xylopia species, has shown a significant cytotoxic activity against breast cancer and epidermal skin cancer cell lines [26].…”
Section: Resultsmentioning
confidence: 99%
“…In a complementary manner, ectopic expression of dominant negative RhoA (RhoA.N19) stimulates junctional remodeling in the absence of steroids. trials as breast cancer therapy, have been shown to inhibit the isoprenylation of RhoA and likely RhoA functionality (78). The Con8 cells used in our study are a tumorigenic mammary epithelial cell line (79), suggesting that utilization of RhoA is distinct from nontumorigenic cells such as the MDCK cell lines.…”
Section: Effects Of Rhoa On the Glucocorticoid-regulated Organizationmentioning
confidence: 87%
“…POH either alone or with PA (perillic acid, the major metabolite of POH in the body), has a potential use as an anticancer drug that stimulates different types of tumors to apoptosis, inhibits their proliferation, or overcomes their resistance to chemo-/radiotherapy (Yuri et al, 2004;Samaila et al, 2004;Elegbede et al, 2003;Clark et al, 2003;Ahn et al, 2003;Bardon et al, 2002;Burke et al, 2002;Bardon et al, 1998). The antitumor activity of POH emanates from its activity of modulating cellular processes that control cell growth and differentiation (Azzoli et al, 2003;Clark et al, 2002;Ariazi et al, 1999;Ren and Gould, 1998;Gould, 1997 andGould, 1995). Thus POH, among other micronutrients, was investigated by the National Cancer Institute (NCI) in NCI-sponsored phase I, II, or III chemoprevention trials for prostate, breast and colon cancers (Greenwald et al, 2002).…”
Section: Cancer Suppressionmentioning
confidence: 99%